ADMINISTRATION OF Curcuma spp. EXTRACT TO CONTROL Aeromonas hydrophila INFECTION IN STRIPED CATFISH (Pangasianodon hypophthalmus) - Sasanti, Ade Dwi; Widanarni, Widanarni; Sukenda, Sukenda; Yuhana, Munti; Wahjuningrum, Dinamella; Setiawati, Mia (Agency for Marine and Fisheries Extension and Human Resources, 2025)
Curcuma spp. is a phytobiotic with potential application in fish farming. This study aimed to evaluate the potential of Curcuma zedoaria, Curcuma aeruginosa and Curcuma mangga extracts in striped catfish infected with Aeromonas hydrophila. The study used a complete randomized design (CRD) consisting of six treatments: KN (negative control), KP (positive control, fish infected without treatment), PE (C. zedoaria extract 6.25 g kg-1), HE (C. aeruginosa extract 6.25 g kg-1), ME (C. mangga extract 6.25 g kg-1) and KE (combination of C. zedoaria extract 2.1 g kg-1 + C. aeruginosa extract 2.1 g kg-1 + C. mangga extract 2.1 g kg-1). A total of 360 striped catfish, 10 ± 0.5 cm were kept in 18 aquariums measuring 50 × 40 × 35 cm3 and fed the treatment for 30 days. The challenge test was conducted on day 31 by injecting A. hydrophila suspension (106 colony-forming units (CFU) mL-1) intramuscularly into fish. The results showed that the treatment administered were able to stimulate the expression of interleukin-1â, interferon-ã 2a, 2b genes, increase the number of red and white blood cells, hematocrit, hemoglobin, phagocytosis activity, respiratory burst, reduce the population of A. hydrophila in the intestine, and reduce tissue damage in striped catfish. Striped catfish treated with the extracts showed significantly higher survival rates (p<0.05) compared to the positive control group. The survival rates were: KN (100.00 %), KP (53.33%), PE (93.33 %), HE (91.67 %), ME (93.33 %), and KE (88.33 %). In conclusion, the treatment administered were able to enhance the immune response and resistance of striped catfish infected with A. hydrophila.